РАСШИРЕНИЕ СОТРУДНИЧЕСТВА В ФЕДЕРАТИВНЫХ ГОСУДАРСТВАХ: ЧЕРЕЗ АСИММЕТРИЮ К ДЕМОКРАТИИ - Шайхутдинова, Гульнара (Вопросы государственного и муниципального управления, 2017)
The article focuses on a comparative analysis of the cooperation mechanisms of a federal center and constituent units based on the constitutional principle of flexibility. Cooperation mechanisms in Switzerland, Canada, the USA and the Russian Federation are studied in detail with the purpose of identifying enhanced cooperation forms and revealing the principle of flexibility influence on these forms. It is determined that enhanced cooperation, based on the treaties between a federal center and constituent units, inevitably leads to asymmetry within the federal system. The hypothesis of the article is that implementation of the principle of flexibility in the form of enhanced cooperation between a federal center and constituent units ensure democratic change and effectiveness of federations. Asymmetric federation as a pluralistic form ensures democratic rights, minorities’ rights, representation and participation. It represents a tool for achieving “unity in diversity”.